Pengaruh Ulasan Pelanggan Online Dan Rating Terhadap Keputusan Pembelian Pada Marketplace Shopee: (Studi Pada Konsumen Shopee Di Bandar Lampung) - Heny Puspita Sari Saputri; Aida Sari; Mudji Rachmat Ramelan (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Widya Gama, 2022)
In today's modern era, technology is developing very rapidly. The rapid development of internet technology has led to new behavioral changes. At first, people like to shop directly at the nearest market, store, and mall, now turning to online shopping. enough with a smartphone and internet connection. The purpose of this study was to determine the effect of online customer reviews and ratings on purchasing decisions on the shopee marketplace in Bandar Lampung. This research uses descriptive research with a quantitative approach. The object of this research is shopee consumers in Bandar Lampung. The method of data collection is through literature review and questionnaires. With a population of shopee consumers in Bandar Lampung and the number of samples is 100 people. The results of this study indicate that there is an influence between online customer reviews and ratings on purchasing decisions at the shopee marketplace in Bandar Lampung.